2006
DOI: 10.1248/bpb.29.766
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Radical-Scavenging Reaction of 2-O-Substituted Ascorbic Acid Derivatives, AA-2G, AA-2P, and AA-2S: A Kinetic and Stoichiometric Study

Abstract: The aim of this study was to characterize the antioxidant activity of three ascorbic acid (AA) derivatives Osubstituted at the C-2 position of AA: ascorbic acid 2-glucoside (AA-2G), ascorbic acid 2-phosphate (AA-2P), and ascorbic acid 2-sulfate (AA-2S). The radical-scavenging activities of these AA derivatives and some common low molecular-weight antioxidants such as uric acid or glutathione against 1,1-diphenyl-picrylhydrazyl (DPPH) radical, 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 39 publications
1
38
1
Order By: Relevance
“…This was consistent with our previous studies. 9,20) Vanillin, ethyl vanillin, and apocynin scavenged little or no DPPH radical or galvinoxyl radical, while vanillyl alcohol and vanillic acid continuously quenched both radicals throughout the experimental period ( Fig. 2A, B).…”
Section: Abtsmentioning
confidence: 96%
See 1 more Smart Citation
“…This was consistent with our previous studies. 9,20) Vanillin, ethyl vanillin, and apocynin scavenged little or no DPPH radical or galvinoxyl radical, while vanillyl alcohol and vanillic acid continuously quenched both radicals throughout the experimental period ( Fig. 2A, B).…”
Section: Abtsmentioning
confidence: 96%
“…We found that 2-O--D-glucopyranosyl-L-ascorbic acid (AA-2G), a stable ascorbic acid derivative, exerted radical-scavenging activity toward unnatural model radicals, including DPPH radical [7][8][9][10] and ABTS radical cation (ABTS þ ). 9,11) The chemical properties of AA-2G as a radical scavenger were widely different from those of ascorbic acid, in that the reaction rate with these model radicals of AA-2G was much slower, but the long-term radical scavenging ability per molecule of AA-2G was superior to that of ascorbic acid. Recently, we reassessed the antioxidant activity of arbutin using five in vitro assay systems, though arbutin has been reported to possess weak antioxidant activity as compared to its precursor, hydroquinone.…”
mentioning
confidence: 99%
“…We have found that AA-2G per se, which had been though to no biological activity, exerted radical-scavenging activity toward unnatural model radicals, such as the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical [13][14][15][16] and the 2,2 0 -azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS þ ). 15,17) The chemical properties of AA-2G as a radical scavenger were largely different from those of AA, in that the reaction rate with these model radicals of AA-2G was far slower than that of AA, but the long-term radical scavenging ability per molecule of AA-2G was superior to that of AA under optimal conditions.…”
Section: Abstract: 2-o--d-glucopyranosyl-l-ascorbicmentioning
confidence: 99%
“…15,17) The chemical properties of AA-2G as a radical scavenger were largely different from those of AA, in that the reaction rate with these model radicals of AA-2G was far slower than that of AA, but the long-term radical scavenging ability per molecule of AA-2G was superior to that of AA under optimal conditions. We also found recently that the radical-scavenging activity of AA-2G was biological relevant using a cell-based antioxidant assay system, 2,2 0 -azobis(2-amidinopropane) dihydrochloride (AAPH)-induced erythrocyte hemolysis inhibition assay.…”
Section: Abstract: 2-o--d-glucopyranosyl-l-ascorbicmentioning
confidence: 99%
“…The DPPH radical-scavenging activities were assessed as described previously 39 with major modification. Briefly, 1.0 mL DPPH radical (0.5 mM) was mixed with 1.0 mL of thymol or dimeric thymol solution (in methanol).…”
Section: Antioxidant Assaymentioning
confidence: 99%